Screen printing plate processing method for improving performance of heterojunction solar cell

By bonding superhydrophobic ionic liquid/silica/polyimide composite film on the heterojunction solar cell screen, the problem of paste adhesion during screen printing is solved, achieving more efficient printing performance and better Low slurry usage.

CN119459103AActive Publication Date: 2025-02-18KUNSHAN SUPERIOR SILK SCREEN PRINTING MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411370690.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-18
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

During the printing process, existing heterojunction solar cell screens are prone to adhesion between paste and screens, resulting in the printing lines being taken away or the paste being attached to the surface of the screen, resulting in the phenomenon of virtual printing or grid breakage.

Method used

A superhydrophobic ionic liquid/silica/polyimide composite film is bonded to the screen plate, and the composite film is coated on the scraper surface and printing surface of the screen plate, and dried and ultraviolet rays are performed. Irradiation cures to form a composite material with low surface energy.

Benefits of technology

It effectively reduces the adhesion between the slurry and the screen plate, reduces the use of the slurry, avoids printing defects, such as blocking or pasting of the screen, and improves the hydrophobic performance and printing reliability of the screen plate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a screen printing plate processing method for improving the performance of a heterojunction solar cell. The screen printing plate processing method comprises the following steps: preparing a super-hydrophobic ionic liquid / silicon dioxide / polyimide composite coating solution; preparing a super-hydrophobic ionic liquid / silicon dioxide / polyimide composite coating solution; coating the coating solution on a scraper surface of a screen printing plate, and drying; coating the film coating solution on the printing surface of a screen printing plate, attaching a film to the printing surface of the screen printing plate, and performing ultraviolet irradiation curing; after curing, the film is taken away, the printing face is washed with water, the needed pattern is formed, and the screen printing plate is manufactured. According to the method, a layer of super-hydrophobic ionic liquid / silicon dioxide / polyimide composite film is adhered to the tensioned screen, so that the performance of the screen is effectively improved, the adhesiveness of the slurry and the screen is reduced, and the use amount of the slurry is greatly reduced during printing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery printing screens, and in particular to a screen processing method for improving the performance of heterojunction solar cells. Background Art

[0002] Resources such as oil and coal are non-renewable resources. With the continuous use and development of the above resources, their reserves on the earth can no longer meet the needs of human social development and progress. At the same time, as air pollution becomes more and more serious, the development of new energy has become a hot topic of common concern to the world. Photovoltaic power generation, as a green energy, has developed rapidly in recent years. Most parts of my country have long sunshine time, which is very suitable for the development of the photovoltaic industry. In recent years, my country has also become a major photovoltaic power generation country. Heterojunction cells, also known as crystalline silicon heterojunction solar cells, are deposited on crystalline silicon amorphous silicon thin films. They combine the advantages of crystalline silicon cells and thin-film cells, and have both the good absorption performance of conventional crystalline silicon cells and the excellent passivation characteristics of thin-film amorphous silicon. Heterojunction solar cells are made of two different materials. Heterojunction cells have the characteristics of high potential for improving photoelectric conversion efficiency, greater cost reduction space, higher bifaciality, effective reduction of heat loss, lower light-induced attenuation, and simple preparation process. They are one of the hot spots for investment in the next generation of solar cells.

[0003] The electrodes of heterojunction solar cells are formed by screen printing, and the structure of the screen includes a screen frame, a mesh and a pattern. The pattern is set on the mesh, the edge of the mesh is fixed in the screen frame, and the mesh is arranged by multiple mesh wires according to certain requirements. At present, in order to improve the life and printability of screen printing, the material of the screen pattern has changed from traditional photosensitive adhesive to polyimide film, and the production process has also changed from exposure-development to laser cutting. The adaptability of polyimide film to various slurries is also stronger than that of traditional photosensitive adhesives, and it has become the mainstream of solar cell screens. However, as the requirements of cell factories to reduce costs and increase efficiency become more and more urgent, the screen pattern becomes finer and the printed film thickness becomes thinner, and the adhesion of the slurry to the silicon wafer becomes lower and lower, resulting in the printed lines being easily taken away by the screen, or the slurry sticking to the surface of the screen, reducing the slurry attached to the silicon wafer, resulting in virtual printing or broken grid phenomenon. Therefore, how to reduce the adhesion of the slurry to the screen has become the focus of research. Summary of the invention

[0004] The technical problem to be solved by the present invention is: in view of the shortcomings of the prior art, a screen processing method for improving the performance of heterojunction solar cells is provided. The method effectively improves the performance of the screen and reduces the adhesion of the slurry to the screen, thereby greatly reducing the amount of slurry used during printing.

[0005] In order to solve the above technical problems, the technical solution of the present invention is:

[0006] A screen processing method for improving the performance of heterojunction solar cells comprises the following steps:

[0007] preparing a super-hydrophobic ionic liquid / silicon dioxide / polyimide composite coating solution;

[0008] Applying the coating solution to the scraper surface of the screen and drying it;

[0009] Apply the coating solution to the printing surface of the screen, attach a film to the printing surface of the screen, and cure it by ultraviolet irradiation;

[0010] After curing, the film is removed and the printed surface is washed with water to form the desired pattern and obtain a screen.

[0011] Preferably, the method for preparing the super-hydrophobic ionic liquid / silicon dioxide / polyimide composite coating solution comprises the following steps:

[0012] (1) adding 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride to a solvent and stirring to mix, then adding an ionic liquid and continuing to stir to obtain a mixed solution;

[0013] (2) mixing tetraethyl orthosilicate and ethanol and stirring them uniformly, then adding APTES and continuing stirring to obtain a dispersion; dissolving 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride in an ethanol solution, heating and hydrolyzing, mixing the obtained hydrolyzate and the dispersion, adding 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, stirring and reacting, filtering the reaction solution after the reaction is completed, and drying the obtained precipitate to obtain modified nano-silica;

[0014] (3) Adding the modified nano-silica to the mixed solution obtained in step (1), subjecting the mixed solution to ultrasonic dispersion treatment, to obtain a coating solution.

[0015] Preferably, in step (1), the molar ratio of the 2,2'-bistrifluoromethyl-4,4'-diaminobiphenyl, 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, and the ionic liquid is 1:1:(1-2).

[0016] Preferably, in step (1), the solvent is one of dimethylformamide and dimethylacetamide.

[0017] Preferably, in step (1), the stirring speed during the stirring and mixing is 1000-2000 rpm, and the stirring time is 10-15 h.

[0018] Preferably, in step (1), the stirring time is continued for 5-10 hours.

[0019] Preferably, in step (2), the usage ratio of tetraethyl orthosilicate, ethanol and APTES is (5-10) g:150 ml:(0.1-0.5) g.

[0020] Preferably, in step (2), the temperature for uniform mixing and stirring is 60-70° C. and the time is 20-30 min.

[0021] Preferably, in step (2), the stirring time is continued for 1-2 hours.

[0022] Preferably, in step (2), the concentration of the ethanol solution is 20-30 v / v%, and the usage ratio of the 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride to the ethanol solution is (0.5-1) g:50 ml.

[0023] Preferably, in step (2), the temperature of the hydrolysis is 65-75°C and the time is 5-10h.

[0024] Preferably, in step (2), the volume ratio of the hydrolyzate to the dispersion is (3-5):1.

[0025] Preferably, in step (2), the mass ratio of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl to 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride is (0.5-0.8):(0.5-1).

[0026] Preferably, in step (2), the stirring reaction is carried out at a temperature of 60-70° C. and for a time of 1-2 h.

[0027] Preferably, in step (3), the mass ratio of the modified nano-silica to the mixed solution is (0.01-0.05):10.

[0028] Preferably, the process of applying the coating solution to the scraper surface of the screen and drying specifically includes: first keeping warm at 60°C for 1 hour, then keeping warm at 80°C for 1 hour, keeping warm at 100°C for 1 hour, and finally keeping warm at 200°C for 1 hour.

[0029] Preferably, in step (3), the thickness of the super-hydrophobic ionic liquid / silicon dioxide / polyimide composite film is 10-20 μm.

[0030] Preferably, the ultraviolet irradiation curing time is 200-400s.

[0031] Preferably, the film layer thickness on the screen scraper surface is 3-8 μm, and the film layer thickness on the screen printing surface is 5-10 μm.

[0032] Due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0033] The present invention modifies the stretched screen by using the prepared super-hydrophobic ionic liquid / silicon dioxide / polyimide composite film, thereby effectively improving the hydrophobicity of the screen, thereby reducing the adhesion between the slurry and the printing screen, avoiding printing defects caused by strong adhesion of the slurry, such as screen clogging or screen sticking, and also reducing the amount of slurry used to a certain extent.

[0034] The present invention uses ionic liquid, modified silicon dioxide and polyimide as a composite film when modifying the screen. The ionic liquid has good thermal stability and chemical stability. When combined with silicon dioxide and polyimide, a composite material with low surface energy is formed. Silicon dioxide provides a rough micro-nano structure, while polyimide gives the composite film good mechanical strength and heat resistance. A microstructure similar to a lotus leaf is formed on the surface of the composite film. This structure can effectively reduce the contact area between the slurry and the solid surface, thereby greatly reducing the adhesion of the slurry. In addition, the microstructure promotes a more localized distribution of the slurry on the surface of the film, thereby reducing the overall adhesion and improving the reliability of printing.

[0035] In addition, polyimide, as a high-performance polymer, has excellent chemical stability and heat resistance, which enables the composite film to maintain a good physical state during the curing process. After curing, the bond between the composite film and the screen will be stronger, forming a mechanical interlocking structure, thereby improving the overall stability of the film. After laser cutting, the composite film has a better cross-sectional quality, further avoiding the problem of slurry adhesion on the cutting edge. DETAILED DESCRIPTION

[0036] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0037] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples. However, it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0038] Unless otherwise specified, the materials in the following examples and comparative examples are commercially available.

[0039] Unless otherwise specified, the experimental conditions in the following methods are conventional experimental conditions in the art.

[0040] Specifically, in the following examples and comparative examples, the leveling agent is Digo Glide 410 leveling agent; the defoaming agent is TEGOFoamex 825 of Digo; the ionic liquid is 1-butyl-3-methylimidazolium hexafluorophosphate.

[0041] In the following embodiments, the method for preparing the stretched screen is as follows:

[0042] S1: Select a tungsten wire mesh with a mesh number of 300 and a wire diameter of 15 μm, and reduce the thickness of the mesh to 20 μm by high-pressure rolling;

[0043] S2: horizontally stretch the mesh on the mesh frame, and stretch the mesh by a mesh-stretching fixture, so that the radial mesh wires and the weft mesh wires after stretching are parallel to the main body directions of two adjacent sides of the mesh frame respectively.

[0044] Example 1

[0045] A screen processing method for improving the performance of heterojunction solar cells comprises the following steps:

[0046] (1) 3 mmol TFMB and 3 mmol 6FDA were added to dimethylacetamide, and the mixture was stirred at 1000 rpm for 15 h. Then, an ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate) was added, and the mixture was stirred for 6 h to obtain a mixed solution.

[0047] (2) 6 g of tetraethyl orthosilicate and 150 ml of ethanol were mixed, stirred at 60° C. for 30 min, 0.5 g of APTES was added to the flask, and stirring was continued for 1 h to obtain a dispersion; 0.91 g of 6FDA was dissolved in 50 ml of 30 v / v% ethanol solution, heated to 70° C. for hydrolysis for 6 h to obtain a hydrolyzate; the above dispersion and hydrolyzate were mixed, 0.66 g of TFMB was added, and the reaction was stirred at 70° C. for 2 h. After the reaction was completed, the reaction solution was cooled to room temperature, and then centrifuged at 3000 rpm for 1 h. The precipitate after centrifugation was dried to obtain modified nano-silica;

[0048] (3) adding 0.1 g of the modified nano-silica to 100 g of the mixed solution obtained in step (1), and subjecting the mixture to ultrasonic dispersion treatment at 500 W for 30 min to obtain a coating solution;

[0049] (4) applying the above coating solution to the scraper surface of the screen, and then keeping the temperature at 60° C., 80° C., 100° C., and 200° C. for 1 h respectively to obtain a first film layer with a thickness of 7 μm;

[0050] (5) Apply the above coating solution to the printing surface of the screen, and attach a film to the printing surface of the screen, and irradiate with ultraviolet light (wavelength of 380-450nm) for curing for 400s; after curing, remove the film, rinse the printing surface with water to form the desired pattern, and obtain a screen with a second film layer with a thickness of 10μm.

[0051] Example 2

[0052] A screen processing method for improving the performance of heterojunction solar cells comprises the following steps:

[0053] (1) 3 mmol TFMB and 3 mmol 6FDA were added to dimethylacetamide, and the mixture was stirred at 2000 rpm for 12 h. Then, an ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate) was added, and the mixture was stirred for 6 h to obtain a mixed solution.

[0054] (2) 6 g of tetraethyl orthosilicate and 150 ml of ethanol were mixed, stirred at 60° C. for 30 min, 0.5 g of APTES was added to the flask, and stirring was continued for 1 h to obtain a dispersion; 0.91 g of 6FDA was dissolved in 50 ml of 30 v / v% ethanol solution, heated to 70° C. for hydrolysis for 6 h to obtain a hydrolyzate; the above dispersion and hydrolyzate were mixed, 0.66 g of TFMB was added, and the reaction was stirred at 70° C. for 2 h. After the reaction was completed, the reaction solution was cooled to room temperature, and then centrifuged at 3000 rpm for 1 h. The precipitate after centrifugation was dried to obtain modified nano-silica;

[0055] (3) adding 0.3 g of the modified nano-silica to 100 g of the mixed solution obtained in step (1), and subjecting the mixture to ultrasonic dispersion treatment at 500 W for 30 min to obtain a coating solution;

[0056] (4) applying the above coating solution to the scraper surface of the screen, and then keeping the temperature at 60° C., 80° C., 100° C., and 200° C. for 1 h respectively to obtain a first film layer with a thickness of 7 μm;

[0057] (5) Apply the above coating solution to the printing surface of the screen, and attach a film to the printing surface of the screen, and irradiate with ultraviolet light (wavelength of 380-450nm) for curing for 400s; after curing, remove the film, rinse the printing surface with water to form the desired pattern, and obtain a screen with a second film layer with a thickness of 10μm.

[0058] Example 3

[0059] A screen processing method for improving the performance of heterojunction solar cells comprises the following steps:

[0060] (1) 3 mmol TFMB and 3 mmol 6FDA were added to dimethylacetamide, and the mixture was stirred at 2000 rpm for 15 h. Then, an ionic liquid (1-butyl-3-methylimidazolium hexafluorophosphate) was added, and the mixture was stirred for 6 h to obtain a mixed solution.

[0061] (2) 6 g of tetraethyl orthosilicate and 150 ml of ethanol were mixed, stirred at 60° C. for 30 min, 0.5 g of APTES was added to the flask, and stirring was continued for 1 h to obtain a dispersion; 0.91 g of 6FDA was dissolved in 50 ml of 30 v / v% ethanol solution, heated to 70° C. for hydrolysis for 6 h to obtain a hydrolyzate; the above dispersion and hydrolyzate were mixed, 0.66 g of TFMB was added, and the reaction was stirred at 70° C. for 2 h. After the reaction was completed, the reaction solution was cooled to room temperature, and then centrifuged at 3000 rpm for 1 h. The precipitate after centrifugation was dried to obtain modified nano-silica;

[0062] (3) adding 0.2 g of the modified nano-silica to 100 g of the mixed solution obtained in step (1), and subjecting the mixture to ultrasonic dispersion treatment at 500 W for 30 min to obtain a coating solution;

[0063] (4) applying the above coating solution to the scraper surface of the screen, and then keeping the temperature at 60° C., 80° C., 100° C., and 200° C. for 1 h respectively to obtain a first film layer with a thickness of 7 μm;

[0064] (5) Apply the above coating solution to the printing surface of the screen, and attach a film to the printing surface of the screen, and irradiate with ultraviolet light (wavelength of 380-450nm) for curing for 400s; after curing, remove the film, rinse the printing surface with water to form the desired pattern, and obtain a screen with a second film layer with a thickness of 10μm.

[0065] In order to better verify that the screen of the present invention has more excellent performance, the following is a detailed description in combination with multiple comparative examples with reference to Example 1.

[0066] Comparative Example 1

[0067] Compared with Example 1, the difference is that no ionic liquid is added in the preparation of the composite membrane, and other conditions are the same as those in Example 1.

[0068] Comparative Example 2

[0069] Compared with Example 1, the difference is that the nano-silicon dioxide is not modified in the preparation of the composite film, and the other conditions are the same as those in Example 1.

[0070] Comparative Example 3

[0071] Compared with Example 1, the difference is that no modified nano-silicon dioxide is added in the preparation of the composite film, and other conditions are the same as those in Example 1.

[0072] Comparative Example 4

[0073] Compared with Example 1, the difference is that modified nano-silica and ionic liquid are not added in the preparation of the composite membrane, and other conditions are the same as those in Example 1.

[0074] After testing, the screen printing times of the screen prepared in the above embodiment is more than 6-8 times that of the screen in comparative example 4, and the service life reaches more than 150,000 times. The screen printing times of the screen prepared in comparative example 1 is 3 times that of the screen in comparative example 4, and the service life reaches 80,000 times. The screen printing times of the screen prepared in comparative example 2 is 2 times that of the screen in comparative example 4, and the service life reaches 50,000 times. The screen printing times of the screen prepared in comparative example 3 is 1.5 times that of the screen in comparative example 4, and the service life reaches 30,000 times.

[0075] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.

Claims

1. A screen processing method for improving the performance of heterojunction solar cells, characterized in that: The following steps are involved: preparing a super-hydrophobic ionic liquid / silicon dioxide / polyimide composite coating solution; Applying the coating solution to the scraper surface of the screen and drying it; Apply the coating solution to the printing surface of the screen, attach a film to the printing surface of the screen, and cure it by ultraviolet irradiation; After curing, the film is removed and the printed surface is washed with water to form the desired pattern and obtain a screen.

2. A screen processing method for improving the performance of heterojunction solar cells according to claim 1, characterized in that: The method for preparing the super-hydrophobic ionic liquid / silicon dioxide / polyimide composite coating solution comprises the following steps: (1) adding 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl and 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride to a solvent and stirring to mix, then adding an ionic liquid and continuing to stir to obtain a mixed solution; (2) mixing tetraethyl orthosilicate and ethanol and stirring them uniformly, then adding APTES and continuing stirring to obtain a dispersion; dissolving 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride in an ethanol solution, heating and hydrolyzing, mixing the obtained hydrolyzate and the dispersion, adding 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, stirring and reacting, filtering the reaction solution after the reaction is completed, and drying the obtained precipitate to obtain modified nano-silica; (3) Adding the modified nano-silica to the mixed solution obtained in step (1), subjecting the mixed solution to ultrasonic dispersion treatment, to obtain a coating solution.

3. A screen processing method for improving the performance of heterojunction solar cells according to claim 2, characterized in that: In step (1), the molar ratio of the 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl, 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride, and the ionic liquid is 1:1:(1-2); and / or the solvent is one of dimethylformamide and dimethylacetamide; And / or the stirring speed during the stirring and mixing is 1000-2000 rpm, and the stirring time is 10-15h; And / or the stirring time is continued for 5-10 hours.

4. A screen processing method for improving the performance of heterojunction solar cells according to claim 2, characterized in that: In step (2), the usage ratio of tetraethyl orthosilicate, ethanol and APTES is (5-10) g:150 ml:(0.1-0.5) g; And / or the temperature for uniform mixing and stirring is 60-70°C and the time is 20-30 minutes. And / or the stirring time is 1-2h.

5. A screen processing method for improving the performance of heterojunction solar cells according to claim 2, characterized in that: In step (2), the concentration of the ethanol solution is 20-30 v / v%, and the usage ratio of the 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride to the ethanol solution is (0.5-1) g:50 ml; And / or the temperature of the hydrolysis is 65-75°C and the time is 5-10h. And / or the volume ratio of the hydrolyzate to the dispersion is (3-5):

1.

6. A screen processing method for improving the performance of heterojunction solar cells according to claim 2, characterized in that: In step (2), the mass ratio of 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl to 2,2'-bis(3,4-dicarboxylic acid)hexafluoropropane dianhydride is (0.5-0.8):(0.5-1); And / or the stirring reaction temperature is 60-70°C and the time is 1-2h.

7. A screen processing method for improving the performance of heterojunction solar cells according to claim 2, characterized in that: In step (3), the mass ratio of the modified nano-silica to the mixed solution is (0.01-0.05):

10.

8. A screen processing method for improving the performance of heterojunction solar cells according to claim 1, characterized in that: The process of applying the coating solution to the scraper surface of the screen and drying it specifically includes: first keeping it warm at 60°C for 1 hour, then keeping it warm at 80°C for 1 hour, keeping it warm at 100°C for 1 hour, and finally keeping it warm at 200°C for 1 hour.

9. A screen processing method for improving the performance of heterojunction solar cells according to claim 1, characterized in that: The UV curing time is 200-400s.

10. The method for processing a screen for improving the performance of a heterojunction solar cell according to claim 1, characterized in that: The film thickness on the screen scraper surface is 3-8 μm, and the film thickness on the screen printing surface is 5-10 μm.

Citation Information

Patent Citations

  • Preparation method for transparent polyimide / silicon dioxide hybrid film

    CN102617875A

  • High-hydrophobicity novel screen printing template and preparation method therefor

    CN111361272A

  • Preparation method of polyimide-silicon dioxide composite aerogel

    CN112892425A

  • Preparation method of highly hydrophobic polyimide film

    CN114196049A

  • Ultralow dielectric porous polyimide film and preparation method thereof

    CN114426698A